Transcriptional Landscape of Cotton Fiber Development and Its Alliance With Fiber-Associated Traits - Prasad, Priti; Khatoon, Uzma; Verma, Rishi Kumar; Aalam, Shahre; Kumar, Ajay; Mohapatra, Debashish; Bhattacharya, Parthasarthi; Bag, Sumit K.; Sawant, Samir V. (Frontiers in Plant Science, 2022)
Cotton fiber development is still an intriguing question to understand the fiber commitment and development. At different fiber developmental stages, many genes change their expression pattern and have a pivotal role in fiber quality and yield. Recently, enormous studies were conducted for transcriptional regulation of fiber and raw data was deposited to the public repository for comprehensive integrative analysis. Here, we remapped >380 cotton RNAseq data with uniform mapping strategies that span ~400 fold coverage to the genome. We identified stage-specific features related to fiber cell commitment, initiation, elongation, and Secondary Cell Wall (SCW) synthesis and their putative cis-regulatory elements for the specific regulation in fiber development. We also mined Exclusively Expressed Transcripts (EETs) that were positively selected during cotton fiber evolution and domestication. Furthermore, the expression of EETs was validated in 100 cotton genotypes through the nCounter assay and correlated with different fiber-related traits. Thus, our data-mining study reveals several important features related to cotton fiber development and improvement which were consolidated in the “CottonExpress-omics” database.